Analisis Hukum terhadap Joki Pinjaman Online Gagal Bayar Perspektif Fatwa DSN MUI No:112/DSN MUI/IX/2017: Studi Kasus pada Aplikasi Tiktok Live - Muhammad Ridho Hakim; Akmaluddin Syahputra (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Online loans have become one of the main forms of consumer financing in today's digital era. However, the growth of the online loan industry also raises concerns with the many polemics that occur within it. This research aims to find out what the legal provisions are for online loan jockeys who fail to pay in the view of DSN MUI NO: 112/DSN MUI/IX/2017. This research method was carried out using an empirical juridical method, so the method used was a field method, namely research carried out in the field aimed at obtaining information and describing events, events with facts found in the field. Data analysis was carried out qualitatively, namely involving observation and in-depth study of the data obtained. The primary data used comes from the field, these are interviews from several online loan jockeys who failed to pay and users of online loan jockey services who failed to pay.This research shows that there are many risks that arise if customers use this default loan jockey service, such as misuse of personal data, getting entangled in new debts and in the perspective of DSN MUI Fatwa NO: 112/DSN MUI/IX/2017stated that the work carried out by the ajir was not in accordance with the principle of muamalah, namely directing jockey service users not to pay the online loan debt at all. Therefore, as an online loan user, do not use this service because it is detrimental to online loan users and in the Fatwa, the work of this service is considered to be contrary to sharia principles.